Defect Analysis and Development Strategy for Robusta Coffee of Tanahwulan Village, Indonesia - Dyah Ayu Savitri; Setiyono; Noer Novijanto; Rizka Maulida Fajriati (Journal La Lifesci, 2022)
Coffee is one of the worthy international trade commodities across countries. Coffee quality is strongly influenced by the behavior of farmers from cultivation, harvesting to processing results. The coffee commodity of Tanahwulan village has a unique character so that it has the potential to be developed further. This study aims to examine the defect of Robusta coffee in Tanahwulan village and its development strategy in the future. For this purpose, the defect analysis based of Indonesian National Standard was used to determine the quality of coffee. The SWOT analysis was also used to identify the development strategy of Tanahwulan village robusta coffee. The results showed that the value of coffee quality defects was at the level of random quality. The types of defects in coffee beans were black bean, partially black bean, broken black bean, brown bean, big size outer skin, medium size outer skin, parchment bean, big size parchment, medium size parchment, small size parchment, broken bean, immature bean , bean with one hole, bean with more than one hole, large sized twigs, dirt or stones and medium sized twigs, dirt or stones. The water content and antioxidant activity were 11% and 82.87%, respectively. The taste of brewed coffee has a final value of 75.5 with notes including chocolaty, spicy, dirty, and dark roast. Based on SWOT Analysis, to improve the Quality of Tanahwulan village robusta coffee, it is necessary to apply aggressive strategy or SO strategy. Therefore, this commodity could empower the opportunities to exist.